Thailand Financial Sector Assessment Program : CPSS Core Principles for Systemically Important Payment Systems - International Monetary Fund; World Bank (World Bank, Washington, DC, 2017)
This assessment of the payment systems in Thailand was undertaken in the context of the International Monetary Fund (IMF) and the World Bank Financial Sector Assessment Program (FSAP) exercise for Thailand in January 2007. It covers the Bank of Thailand Automated High-value Transfer Network (BAHTNET), which is a real time gross settlement (RTGS) system. The Bank of Thailand (BOT) conducted a comprehensive self-assessment of BAHTNET observance of the Core Principles for Systemically Important Payment Systems (CPSIPS). It was professionally done and was made available to the mission in advance. The Thai authorities were fully cooperative and all relevant documentation to fulfill the assessment of BAHTNET was provided on time and without difficulties. The logistical support and warm hospitality of the officials of the BOT are greatly appreciated.